An Analysis on Studentsâ Motivation in English Reading: A Descriptive Study to the Students of English Study Program in the Academic Year 2013/2014 - Firmansyah, Ari (West Kalimantan Scholars: Studies on English Language and Education, 2015)
The purpose of this research was to investigate the studentsâ motivation in English reading. The population of this research was 210 students. The researcher took 136 students as the participants of this research by using simple random sampling. Two tools were used in data collection. First, a questionnaire was distributed to 136 students to investigate aspects which influence studentsâ motivation in English reading. The second tool was interview. The interview was conducted to 4 students to know the reasons which influence studentsâ motivation in English reading. The questionnaire result showed that the students were intrinsically motivated and the result of interview proved that besides to add knowledge, or learn culture, most of them answered that their motivation was to add new vocabulary. In order to promote learnersâ intrinsic motivation, the best way might be by providing them with interesting material.